(untitled) (International Journal of Current Engineering and Technology, 2014)
Through this review, I present theories of Cloud Computing and its framework for implementing cloud computing technology across NASA. This review include case study with issues and complexities of using cloud computing platform NEBULA in NASA. It is open source platform for building cloud services (offered by Google, Amazon) using OpenStack (a Linux for cloud computing) for providing instant access to virtual machines for storing huge digital data. For operating Nebula cloud, OpenStack offers 3 pillars for computing, storing and networking which includes services like image management, identity and web interface. Nebula has limited beta and NASA is looking for beta testers to test driving cloud.